Sex differences in the use of asthma drugs: cross sectional study. Issue 7170 (21st November 1998) - Sexton, Mary; Althuis, Michelle D; Santanello, Nancy; Hyndman, Sophie; Williams, Rhys; Schmeidler, David
Abstract : Objectives: To assess the use of asthma drugs by men and women with asthma and to identify sex specific predictors for the use of oral steroids. Design: Cross sectional study. Setting: Six general practicesin East Anglia. Subjects: 103 men and 134 women aged 20-54 with asthma. Main outcome measures: Self reported use of β agonists, inhaled steroids, and oral steroids. Results: No sex difference was found in use of β agonists or inhaled steroids. However a strong association existed between sex and oral steroid use. 40 (30%) women reported using oral steroids compared with nine (9%) men. Women were more than five times (odds ratio=5.5, 95% confidence interval 2.2 to 13.7) more likely to report use of oral steroids than men after asthma symptoms, age, visits to the general practitioner in previous six months, and time since diagnosis of asthma were controlled for. Women who had visited the general practitioner for asthma one or more times in the previous six months were four times (3.9, 1.6 to 9.5) as likely to report use of oral steroids. In addition, more frequent visits to the general practitioner for asthma were related in a dose-response manner to a greater likelihood of using oral steroids among women after asthma symptoms, age, and time since diagnosis were controlled for. This relation was not observed among men. Conclusion: Women used oral steroids more than men. The more frequent consultations with a doctor by women may result in more requests for oral steroids or doctors may preferentially prescribe oral steroids to women.